2023
DOI: 10.2478/helm-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Blastocystis sp. among cooks in the region of Fez-Meknes (Morocco)

M. Boutahar,
M. Er-Rami,
M. Belaouni

Abstract: Summary Cooks have an important role in the dissemination and transmission of enteropathogenic microorganisms, including intestinal parasites such as Blastocystis sp. responsible for blastocystosis. Blastocystis is a unicellular, anaerobic, eukaryotic protist that colonizes the intestinal tract of many hosts. It is the most common parasite found in human stool. It can be the cause of acute digestive disorders which could lead to chronic syndromes such as irritable bowel syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Statistically signi cant values are indicated in bold. Using the same detection method, a recent study conducted by our research group has reported a Blastocystis prevalence of 39.8% among food handlers in the region of Fez-Meknes(Boutahar et al 2023) Darwish et al 2023),. in paediatric populations in Nigeria(Poulsen et al 2016), and in apparently healthy individuals in Qatar (Abu-Madi et al 2015).…”
mentioning
confidence: 99%
“…Statistically signi cant values are indicated in bold. Using the same detection method, a recent study conducted by our research group has reported a Blastocystis prevalence of 39.8% among food handlers in the region of Fez-Meknes(Boutahar et al 2023) Darwish et al 2023),. in paediatric populations in Nigeria(Poulsen et al 2016), and in apparently healthy individuals in Qatar (Abu-Madi et al 2015).…”
mentioning
confidence: 99%